Akuisisi Bahasa Arab Santri Pondok Pesantren Madinah Karya Tani Lampung Timur - J. Sutarjo; Novita Rahmi; Dian Ekawati; Nawang Wulandari (Institut Agama Islam Negeri (IAIN) Metro, 2021)
One of the Islamic boarding schools that teaches Arabic with divine and active competence is Madina Islamic Boarding School, which is located in Karya Tani Labuhan Meringgai, East Lampung. Many aspects certainly support the success of the institution that implements and develops Arabic language learning This reserch used a psycholinguistic perspective, especially language acquisition. This is because in fact the graduates of the Medina Islamic Boarding School have active Arabic language competence. It is very interesting to conduct a study to find out about the language acquisition of the students at the Islamic boarding school. This study describes; 1) Arabic language learning process, 2) Arabic language acquisition process, 3) acquisition theory relevance in a psycholinguistic perspective with the Arabic language learning process, and 4) strengths and weaknesses of the Arabic acquisition process at the Madinah Islamic Boarding School. This research is a qualitative field research. For data collection using the observation method, interview method, and documentation method. From this study, it is hoped that it will become one of the references in developing Arabic learning. From the results of the study, it can be concluded that the acquisition of foreign languages, especially Arabic, for the students of the modern Islamic boarding school Madinah, was carried out through formal and naturalistic presentations. For the factors that affect the Arabic language acquisition process, there are obstacles to the motivation of students which also affect the Arabic language environment which is less conducive. As for the age factor, the presentation of learning and the first language of the students have been conditioned and in accordance with the ideal foreign language acquisition process in a psycholinguistic perspective. The age of children to adolescents is the ideal age to carry out the process of acquiring foreign languages, presenting complete learning in a formal and naturalistic manner, as well as conditioning the first language by speaking Arabic in the first year of students studying at Islamic boarding schools.